Potential ecological hazards assessment and prediction of sediment heavy metals pollution along the Gulf of Suez, Egypt - Mohamed I.A. Ibrahim; Laila A. Mohamed; Manal G. Mahmoud; Kholoud S. Shaban; Mamdouh A. Fahmy; Mahmoud H. Ebeid (Egyptian Journal of Aquatic Research, 2019)
In this study, heavy metals Cr, Fe, Ni, Cu, Zn, Pb, Cd and Hg in surface sediments were collected from 14 hot spot locations inside the Gulf of Suez to assess the levels of contamination posed by heavy metals. The general trend for the mean concentrations of the investigated heavy metals in sediments followed the order: Fe > Zn > Ni > Pb > Cr > Cu > Cd > Hg. The heavy metals contamination was assessed using pollution indices: modified degree of contamination (mCd), potential ecological risk index (RI), mean effect range median quotient (MERM-Q), toxicity degree index (STd) and toxicity load index (TLI). Generally, based on the values of mCd, RI, MERM-Q as well as STd indices, considerable and intense pollution of heavy metals in sediments through the whole study area was not found. The multivariate analyses showed that Fe, Cu, Zn, Pb and Cd are originating from various maritime activities along the Gulf of Suez, while Cr and Ni mainly originating from natural sources with minor contributions from maritime activities. Keywords: The Gulf of Suez, Sediment, Contamination indices, Heavy metals